Factors Associated With E. coli Levels in and Salmonella Contamination of Agricultural Water Differed Between North and South Florida Waterways - Murphy, Claire M.; Strawn, Laura K.; Chapin, Travis K.; McEgan, Rachel; Gopidi, Sweeya; Friedrich, Loretta; Goodridge, Lawrence D.; Weller, Daniel L.; Schneider, Keith R.; Danyluk, Michelle D. (Frontiers in Water, 2022)
The microbial quality of agricultural water is often assessed using fecal indicator bacteria (FIB) and physicochemical parameters. The presence, direction, and strength of associations between microbial and physicochemical parameters, and the presence of human pathogens in surface water vary across space (e.g., region) and time. This study was undertaken to understand these associations in two produce-growing regions in Florida, USA, and to examine the pathogen ecology in waterways used for produce production. The relationship between Salmonella presence, and microbial and physicochemical water quality; as well as weather and land use factors were evaluated. Water samples were collected from six sites in North Florida (N = 72 samples) and eight sites in South Florida (N = 96 samples) over 12 sampling months. Land use around each sampling site was characterized, and weather and water quality data were collected at each sampling. Salmonella, generic Escherichia coli, total coliform, and aerobic plate count bacteria populations were enumerated in each sample. Univariable and multivariable regression models were then developed to characterize associations between microbial water quality (i.e., E. coli levels and Salmonella presence), and water quality, weather, and land use factors separately for North and South Florida. The E. coli and total coliforms mean concentrations (log10 MPN/100 mL) were 1.8 ± 0.6 and >3.0 ± 0.4 in North and 1.3 ± 0.6 and >3.3 ± 0.2 in South Florida waterways, respectively. While Salmonella was detected in 23.6% (17/72) of North Florida and 28.1% (27/96) of South Florida samples, the concentration ranged between <0.48 and 1.4 log10 MPN/100 mL in North Florida, and <0.48 and 3.0 log10 MPN/100 mL in South Florida. Regression analyses showed no evidence of a correlation between either log10 total coliforms or E. coli levels, and if a sample was Salmonella-positive. The factors associated with Salmonella presence and log10E. coli levels in North Florida differed from those in South Florida; no factors retrained in multivariable regression models were the same for the North and South Florida models. The differences in associations between regions highlight the complexity of understanding pathogen ecology in freshwater environments and suggest substantial differences between intra-state regions in risk factors for Salmonella contamination of agricultural water.